A Study on the Translation and Promotion of Decoded in English-Speaking Countries—From the Perspective of Socio-Translation - Shuwen Dong (Journal of Linguistics and Communication Studies, 2024)
Since there are few studies on the translation and promotion of Decoded based on Socio-Translation, this thesis adopts Field Theory and Actor-Network Theory to study the following questions: 1) What kinds of capitals do the author, translator and publishing houses that contributed to the translation and promotion of Decoded? 2) What kinds of habitus do those three have to promote this process? 3) What are the characteristics of this actor-network? This paper adopts the literature research and example analysis methods. It is found that 1) The cultural capitals and symbolic capitals of the author Mai Jia, the cultural capitals and social capitals of the translator Milburn, and the economic capitals, symbolic capitals and social capitals of the publishing houses Penguin Press and FSG play important roles to promote this process to be successful. 2) The key habitus. Mai Jia: espionage and decoding writing theme, unique writing style and writing skills which are suitable for English readers. Milburn: interest of translating spay novels, the translation concept of non-profit and translation strategy according with the reading habits of English readers. Penguin Press and FSG: Spending much money on publicity. All these promote the whole process of translation and promotion. 3) The characteristics of this actor-network: It was unconscious for the translator to initiate the translation, something incidental happened in the process of spread, but there was no communication between the author and translator in the process of translation initiation and publishing. In spite of limitations in this study, the writer sincerely hopes that the results of this paper can provide some reference for other Chinese literary works to enter the English-speaking world successfully.